PENGARUH PERSUASI ATAS PREFERENSI KLIEN DAN PENGALAMAN AUDIT TERHADAP PERTIMBANGAN AUDITOR DALAM MENGEVALUASI BUKTI AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA DENPASAR - Putu Ady Ariartha; I Gst. Ayu Diah Utari (Universitas Pendidikan Nasional, 2017)
Asian Economic Community (AEC) is the thought of the leaders of the Southeast Asian region, which will make their international level competition for professional people especially public accountant. Public accounting firm that works in the KAP is needed in order to assess whether the financial statements of a company have been presented fairly and can be accounted in accordance with the applicable standard. The purpose of this study was to determine the effect of persuasion on client preferences, experience an audit of the auditor's judgment in evaluating audit evidence. The study was conducted on 8 KAP in Denpasar with a total population of 75 auditors. The research instrument used questionnaire. Data collected was processed using a computer program using multiple linear regression analysis technique. The results showed significant influences of persuasion on client preferences (X1) on the auditor's judgment in evaluating audit evidence. There is a significant effect of audit experience (X2) on the auditor's judgment in evaluating the audit evidence. There is a simultaneous influence of persuasion on client preferences (X1) and audit experience (X2) on the auditor's judgment in evaluating audit evidence. Keywords: Persuation On Client Preference, Experience Of Audit, Judgment Auditor